2006
DOI: 10.1002/ajh.20758
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ALK+ anaplastic large cell lymphoma with t(3;8)(q26.2;q24) translocation and c‐myc rearrangement terminating in a leukemic phase

Abstract: Pediatric ALK-positive anaplastic large cell lymphoma (ALK+ ALCL) is usually associated with a favorable prognosis. ALK+ ALCL associated with a leukemic phase is uncommon, but has been associated with an aggressive clinical course and unfavorable prognosis. Overexpression of c-myc has been shown to be a consistent finding in ALK+, but not ALK-negative ALCL (ALKÀ ALCL), and the c-myc gene is considered a downstream target of deregulated ALK signaling. We describe a pediatric ALK+ ALCL with a leukemic phase at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Although many ALK+ ALCL patients reach clinical remission, few refractory {Savage, 2008 #1044} and rare aggressive forms, carrying translocations or copy number gains of MYC {Monaco, 2007 #939}, have been described {Grewal, 2007 #790;Monaco, 2007 #939;Liang, 2013 #1195;Moritake, 2011 #941}.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although many ALK+ ALCL patients reach clinical remission, few refractory {Savage, 2008 #1044} and rare aggressive forms, carrying translocations or copy number gains of MYC {Monaco, 2007 #939}, have been described {Grewal, 2007 #790;Monaco, 2007 #939;Liang, 2013 #1195;Moritake, 2011 #941}.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of TP53 , PRDM1/Blimp1 {Boi, 2013 #1207} and TP63 {Vasmatzis, 2012 #1132} and deregulated expression of MYC {Monaco, 2007 #939} might pinpoint at diagnosis refractory/relapse or even aggressive forms of ALCL. In our PDT model, the emergency of subclones carrying defects of PRDM1/Blimp1 and MYC support the hypothesis that these lesions may have a relevant pathogenetic role and might occur as additional event along tumorigenesis contributing to more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Translocations affecting MYC are infrequent in these lymphomas and seem to be associated with an aggressive clinical course. [39][40][41] In contrast, a recent study using array comparative genomic hybridization on primary ALCL samples reported recurrent MYC gains. 42 In addition, other MYC upregulating mechanisms may be used by ALCL.…”
Section: Discussionmentioning
confidence: 99%